Early Diagnosis Of Benign Tumors Of The Nasopharynx - Lutfullaev Umrillo Lutfullaevich; Kobilova Shahodat Shokirovna; Madaminova Nigora Ergashevna; Narziev Mamurjon Musirmonovich; Makhmudova Maftuna Shokirovna (Zien Journals, 2024)
Improving early diagnosis of nasopharyngeal tumors will allow to treat this category of patients effectively. In a large clinical material held clinical course of the data analysis and given a detailed assessment of each of the methods of diagnosis of tumors of the nasopharynx. It was concluded that the feasibility of using fiberoptic endoscopy for early detection of benign tumors of the nasopharynx
Keywords: nasopharyngeal tumor; symptoms; diagnosis